PENGEMBANGAN PENYULUH KELUARGA BERENCANA - ', Erinaldi (JIANA ( Jurnal Ilmu Administrasi Negara ), 2016)
Development of Family Planning Counseling. This study aims to describe and analyze the implementation of the development of family planning officer at Family Planning Agency for Women’s Empowerment and Child Protection (BKBPPPA) Kota Dumai and factors that influence it. This research is descriptive qualitative interviews in (in-depth interviews) and observation. Informants in this study is the Head KBPPPA Dumai, Secretary, Head of Sub Division Officer, Head of Family Planning and Family Welfare, KB counseling and Kader Posyandu. Data analysis techniques through the procedure of the presentation of the data, data reduction and conclusion. The results showed counseling Development Implementation KB less than optimal seen from authority, Task Variety, Task Identity Task Significance and Feedbeck. Factors affecting the development of the implementation of the family planning officer in Kota Dumai is the absence of a commitment to provide the contribution feedbeck family planning officer, lack of attention to the needs of education facilities and infrastructure, and lack of control on discipline KB counseling as well as the lack of effective implementation of education and training.